2013
DOI: 10.1176/appi.ajp.2013.12111484
|View full text |Cite
|
Sign up to set email alerts
|

Neural Substrates of Treatment Response to Cognitive-Behavioral Therapy in Panic Disorder With Agoraphobia

Abstract: This study identified brain activation patterns associated with treatment response in patients with panic disorder with agoraphobia. Altered safety signal processing and anterior cingulate cortex-amygdala coupling may indicate individual differences among these patients that determine the effectiveness of exposure-based CBT and associated neuroplastic changes. Findings point to brain networks by which successful CBT in this patient population is mediated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
89
0
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 118 publications
(99 citation statements)
references
References 33 publications
9
89
0
1
Order By: Relevance
“…These data indicate that different top down and bottom-up processes during fear conditioning 55 are affected by genetically driven CRHR1 expression differences in patients with PD/AG. Especially the generalization of fear and dysfunctional safety signal processing has been considered to be a relevant pathological mechanisms of PD/AG 68 and has been shown to be associated to treatment response 54 . Altogether, these data indicate that variation in CHRH1 genotypes and subsequent expressional changes might contribute to the development of sustained fear due to impaired safety signaling processing and increased amygdala reactivity towards neural stimuli.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data indicate that different top down and bottom-up processes during fear conditioning 55 are affected by genetically driven CRHR1 expression differences in patients with PD/AG. Especially the generalization of fear and dysfunctional safety signal processing has been considered to be a relevant pathological mechanisms of PD/AG 68 and has been shown to be associated to treatment response 54 . Altogether, these data indicate that variation in CHRH1 genotypes and subsequent expressional changes might contribute to the development of sustained fear due to impaired safety signaling processing and increased amygdala reactivity towards neural stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…A Monte Carlo simulation was conducted to establish an appropriate voxel contiguity threshold 53 . Thus, for all analyses voxels with a significance level of p < 0.005 uncorrected belonging to clusters with at least 142 voxels are reported (see also 51,52,54,55 ). Whole-brain analysis was carried out first.…”
Section: Functional Mrimentioning
confidence: 99%
“…Particularly in PD, two resting positron emission tomography studies demonstrated change in glucose utilization in distributed regions of predominantly the medial and lateral frontal and temporal cortices in CBT groups of 6 [2] and 11 patients [3]. Besides our own [1,30], the only other fMRI study [48] used an emotional linguistic go/nogo design in 9 patients with PD following short-term psychodynamic inpatient treatment (4 weeks), after treatment symptoms had improved, and frontolimbic activation patterns had been normalized. Despite the small sample sizes and only partially overlapping results, these studies indicate that different forms of psychotherapy can influence processes in the brain in patients with PD.…”
Section: Introductionmentioning
confidence: 90%
“…Thus, the advantage of going with the patient out into the field during exposure might be mediated by different encoding or learning strategies, possibly also leading to a better cognitive awareness of contingencies for external and internal events. The investigation of the neural correlates of learning mechanisms such as exteroceptive fear conditioning in PD/AG can help to understand CBT-related changes on the brain level [1,28,29,30]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation